Organizational Learning Capabilities and Adaptive Performance of Public Elementary School Teachers - Gea M. Mapansa; Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between organizational learning capabilities and adaptive performance among public elementary school teachers in Caraga South District, Division of Davao Oriental. A descriptive-correlational research design was employed, involving 98 teachers from various public elementary schools in the district. Data were gathered using standardized questionnaires: the Organizational Learning Capabilities Scale by Obeso et al. (2023) and the Adaptive Performance Scale by Inbaraj and Jatin (2020). The instruments underwent reliability testing prior to administration. Results showed that both organizational learning capabilities and adaptive performance were rated at very extensive levels. Correlation analysis revealed a significant positive relationship between organizational learning capabilities and adaptive performance (R = 0.71, p = 0.000). Furthermore, multiple regression analysis indicated that specific domains—systems perspective, openness and experimentation, and knowledge transfer and integration—significantly influenced adaptive performance (R = 0.720, p = 0.000). Based on these findings, it is recommended that school administrators strengthen professional development initiatives that emphasize continuous learning, innovation, and effective knowledge-sharing practices. In conclusion, fostering strong organizational learning capabilities can meaningfully enhance teachers’ adaptive performance, equipping them to respond to the dynamic demands of the education sector effectively.